Antioxidant effects of ethyl acetate extract of Desmodium gangeticum root on myocardial ischemia reperfusion injury in rat hearts - Raman Archana; Suryanarayanan Srilalitha; Kurian Gino A; Padikkala Jose (BMC, 2010)
Abstract Background This study aims to evaluate the antioxidant potential of the ethyl acetate extract of Desmodium gangeticum root for cardioprotection from ischemia reperfusion-induced oxidative stress. Methods The in vitro antioxidant potential of the extract was in terms of hydroxyl radical scavenging activity, lipid peroxide scavenging activity, nitric oxide scavenging activity and diphenylpicrylhydrazyl radical scavenging activity. The in vivo antioxidant potential of the extract was assessed in an isolated rat heart model. Results Free radicals were scavenged by the extract in a concentration-dependent manner within the range of the given concentrations in all models. Administration of the ethyl acetate extract of Desmodium gangeticum root (100 mg per kg body weight) before global ischemia caused a significant improvement of cardiac function and a decrease in the release of lactate dehydrogenase in coronary effluent, as well as the level of malondialdehyde in myocardial tissues. Conclusion The ethyl acetate extract of Desmodium gangeticum root protects the myocardium against ischemia-reperfusion-induced damage in rats. The effects of the extract may be related to the inhibition of lipid peroxidation.